Potensi Ekstrak Daun Asam Jawa (Tamarindus indica L) dalam Menghambat Pertumbuhan Bakteri Streptococcus mutans pada Resin Akrilik Heat-cured - Raissa Salma Hardiani; Achmad Gunadi; Depi Praharani; Rahardyan Parnaadji; Nadie Fatimatuzzahro (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Heat-cured acrylic resin is a material that is often used as a denture base. However, heat-cured acrylic resin is porous which can be a site for plaque accumulation. Streptococcus mutans is a microorganism that initiates plaque formation. Therefore, the cleanliness of the denture must always be maintained, one of which is by immersing the denture in 0.5% NaOCl solution. However, NaOCl can fade the color of acrylic resin and is corrosive. Alternative materials that can be used are materials derived from nature. Tamarind leaves are known to contain bioactive compounds that have antibacterial activity. The purpose of this study is to determine the potential of tamarind leaf extract at several concentrations that could inhibit the growth of S. mutans on heat-cured acrylic resin and the concentration that had the greatest ability to inhibit the growth of S. mutans on heat-cured acrylic resin. This type of research is a laboratory experimental study with a post-test-only control group design. Each acrylic resin plate will be contaminated with S. mutans for 24 hours and then immersed in the tamarind leaves extract concentration of 3.125%; 6.25%; 12.5%; 25%, positive control (NaOCl 0,5%), and negative control. The measurement of the number of S. mutans was carried out using a spectrophotometer. . The results showed that tamarind leaf extract was able to inhibit the growth of S. mutans on heat-cured acrylic resin and the highest concentrations in inhibiting the growth of S. mutans on heat-cured acrylic resin were 12.5% and 25%.